Afforestation, Subsequent Forest Fires and Provision of Hydrological Services: A Model‐Based Analysis for a Mediterranean Mountainous Catchment. (5th September 2017) - Nunes, João Pedro; Naranjo Quintanilla, Paula; Santos, Juliana Marisa; Serpa, Dalila; Carvalho‐Santos, Cláudia; Rocha, João; Keizer, Jan Jacob; Keesstra, Saskia Deborah
Abstract: Mediterranean landscapes have experienced extensive abandonment and reforestation in recent decades, which should have improved the provision of hydrological services such as flood mitigation, soil erosion protection and water quality regulation. However, these forests are fire‐prone, and the postfire increase in runoff, erosion and sediment exports could negatively affect service provision. This issue was assessed by using the Soil and Water Assessment Tool model for the Macieira de Alcôba mountain catchment in northwestern Portugal, covered by agriculture and forest plantations, monitored in 2010–2014 and partially burnt in 2011. The model was validated for streamflow, sediment yield and erosion in agricultural fields and burnt hillslopes, showing that it can be adapted for postfire simulation. Model results for a decadal assessment (2004–2014) show that the fire increased erosion in the burnt slopes from 0.1 to 46.5 Mg ha −1  y −1 and catchment sediment yield from 0.14 to 2.1 Mg ha −1  y −1 . Erosion in the burnt forest during this decade was 1 order of magnitude above that in agricultural fields. Model results for different fire and land‐use scenarios indicate that postfire erosion and sediment yield were lower without postfire soil management for reforestation and when the fire occurred in pine forests (land use before the 1990s) or in shrublands (land‐use before afforestation in the 1930s). These impacts were robust to changes in postfire weather and to a longer (20 years) unburnt period. The results suggest that, in the long term, Mediterranean fire‐prone forests might not provide the anticipated soil protection and water quality regulation services. Copyright © 2017 John Wiley & Sons, Ltd.